Effectiveness of internal audit: ensuring public sector accountability and integrity / Nor Raihana Asmar Mohd Noor ...[et al.] - Mohd Noor, Nor Raihana Asmar; Kamarul Zaman, Liziana; Wan Mustapha, Wan Asma Hanim (Universiti Teknologi MARA, Kedah, 2017)
Good governance in public administration does have the positive impacts to the public. Government practices and implements good service delivery because they want to uphold the status of public servant as it is the main obligation of government to serve the best to the public. These activities are monitored by the internal audit to achieve accountability and integrity, to improve the implementation of government programs and to develop confidence among citizens and stakeholders as well as to cater to any risk of mismanagement of public fund. This paper focuses on reviewing the previous literatures in determining the determinants in assessing the effectiveness of internal auditing process in the public sector. Therefore, this paper uses secondary data in gathering the information relating to the internal audit to accomplish the objectives of this study. This paper further expands and develops the literature on the role and effectiveness of internal auditing to enhance public sector accountability and integrity. Eventhough the paper is conceptual, but it also concludes the factors that contribute to the effectiveness of internal audit. Therefore, this study finds that the effectiveness of internal audit in public sector can be measured through several factors such as auditors' competency, independence of internal auditor and management support to the role of the internal auditor.